2018
DOI: 10.15537/smj.2018.4.21473
|View full text |Cite
|
Sign up to set email alerts
|

How often do children receive their vaccinations late, and why?

Abstract: Objectives:To assess vaccination timeliness, risk factors associated with delays and the reasons for delayed vaccinations among children below the age of 3 years in Jeddah, Kingdom of Saudi Arabia.Methods:This is a cross-sectional study conducted in Jeddah, Saudi Arabia during the period of May 2016 to August 2017. Data were obtained from parents of children under the age of 3 years using a structured questionnaire comprised of questions about sociodemographics, physical well-being of the child and the reasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 22 publications
5
26
5
Order By: Relevance
“…No significant association was found between gender and immunization completeness, as in different countries, [20][21][22] thus it appears that there was no gender discrimination in immunization. The current study results are consistent with those of Saudi Arabia and another study in Mosul, 16,17 in which birth weight did not influence immunization status.…”
Section: Factors Influencing Compliance With Immunization Regimensupporting
confidence: 92%
See 2 more Smart Citations
“…No significant association was found between gender and immunization completeness, as in different countries, [20][21][22] thus it appears that there was no gender discrimination in immunization. The current study results are consistent with those of Saudi Arabia and another study in Mosul, 16,17 in which birth weight did not influence immunization status.…”
Section: Factors Influencing Compliance With Immunization Regimensupporting
confidence: 92%
“…The immunization incompleteness rate observed in this study was (29.8%) which is comparable to the rate observed in Jeddah, Saudi Arabia (24.2%) , 16 while a study conducted in Mosul-Iraq revealed that the percentage of children with partial immunization was (54.2%) in 2017. 17 A study done in India on children below the age of 5 revealed that over 50% of them were delayed.…”
Section: Immunization Incompletenesssupporting
confidence: 72%
See 1 more Smart Citation
“…Data on immunization were collected from the child's vaccination card. The outcome variable was compliance with the vaccination schedule, which was considered adequate when the doses of vaccine received were in accordance with the 2015 national immunization program's recommendations and inadequate if the doses of the vaccine had not been administered within 30 days of the recommended date, as defined in a similar study [18].…”
Section: Methodsmentioning
confidence: 99%
“…The outcome variable was vaccination schedule status, categorized as complete if the child had received the total number of doses of each vaccine scheme for age in accordance with the 2015 National Childhood Immunization Schedule of the Brazilian Ministry of Health (Additional le 1), otherwise as incomplete if the doses of the vaccine had not been administered within 30 days of the established date for all age groups, as referenced in a similar study [19]. Data on immunization were collected, exclusively, from the child's vaccination card records, shown by all participating children to the interviewers in the original research.…”
Section: Outcomementioning
confidence: 99%